Second law analysis in a three dimensional lid-driven cavity - Lioua, Kolsi; Öztop, Hakan Fehmi; Borjini, Mohamed Naceur; Al-Salem, Khaled (Pergamon-Elsevier Science Ltd, 2011)
Three dimensional analyses of laminar mixed convection and entropy generation in a cubic lid-driven cavity have been performed numerically. Left side of cavity moves in + y (Case I) or -y (Case II) direction. The cavity is heated from left side and cooled from right while other surfaces are adiabatic. Richardson number is the main parameter which changes from 0.01 to 100. Prandtl number is fixed at Pr = 0.71. Results are presented by isotherms, local and mean Nusselt number, entropy generation due to heat transfer and fluid friction, velocity vectors and Bejan number. Total entropy generation contours are also presented. It is found that direction of lid is an effective parameter on both entropy generation and heat and fluid flow for low values of Richardson number but it becomes insignificant at high Richardson number. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Entropy generation; Lid-driven cavity; Mixed convection